Poisoning and suicide attempts in adolescent girls - a problem we need to be aware of - Tomkiewicz, Maria; Tomkiewicz, Maciej; Sosnowska, Weronika; Brzozowska, Aleksandra; Tchórz, Michał; Taracha, Kalina; Tkaczyk, Rafał; Tomczyk, Jakub; Świątek, Gabriela (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Poisoning among children and adolescents is occurring on an ever-increasing scale. Women are particularly susceptible to intentional poisoning, and they predominate in the statistics of self-poisoning. The aim of the study is to analyze cases of poisoning in girls under 18 years of age hospitalized in the Clinical Toxicology and Cardiology Department of the Stefan Cardinal Wyszynski Regional Hospital in Lublin in 2022, taking into account the type of substance ingested, the place of residence of the patients and comorbidities. Material and methods: The study was retrospective in nature. It used the analysis of medical records of 84 cases of intoxication in girls under 18 years of age. Results: During the time period studied, 84 girls aged 13-18 were hospitalized for poisoning. Most of the cases were urban residents (64.3%). The toxic substances causing poisoning were mainly drugs (63.1%), narcotics (17.9%) and ethanol (17.8%). Poisoning of an intentional nature involved 80 (95.2%) cases, 37 (44%) cases were suicide attempts. In 54 (64.3%) cases, the patient was burdened with a mental illness, the most common being depressive disorders. There were no deaths in the study group. Conclusions: Due to the increasing phenomenon of mental disorders, as well as intentional poisoning among adolescent girls, special emphasis should be placed on psychological care, pedagogical care, of girls in adolescence. This is the time when girls have problems with acceptance of their bodies, with acceptance among peers. Parents and teachers should be made aware of this.